"Drugs and alcohol get talked about, why not betting?" Young men's qualitative insights about strategies to prevent gambling harm. Issue 2 (7th August 2022) - Nyemcsok, Christian; Pitt, Hannah; Kremer, Peter; Thomas, Samantha L.
Abstract: Issues addressed: Research is needed to understand young people's perspectives about public health promotion strategies relevant for their health and wellbeing. This study provides suggestions from young male gamblers about sports betting harm prevention and reduction strategies. Methods: In‐depth interviews were conducted with 16 young men aged 18 to 24 years, from Melbourne, Victoria, who regularly engaged in sports betting. A critical qualitative inquiry approach, using methods of constructivist grounded theory guided the study. Reflexive thematic analysis was used to interpret and construct themes from the data. Results: Participants indicated three main harm prevention strategies. These were online consumer protection and regulatory strategies, public education campaigns that highlighted sports betting risks and harms and the creation of formal and informal support networks to reduce stigma and encourage help seeking. They also supported being engaged in the development of harm prevention strategies and suggested ways to help reduce barriers to engagement. Conclusion: Young men recognise the need for regulatory, education and engagement responses to counter the risks posed by new gambling products. Young men may be difficult to engage in formal prevention activities, however, youth‐led and informal interactive mechanisms may help to overcome this barrier, and contribute to a comprehensive public health approach to gambling harm prevention. So what?: Young men can draw upon their lived experiences of gambling to provide insights relevant for public health promotion. Mechanisms should be developed to engage young people in the co‐production of strategies and policies aimed at gambling harm prevention and reduction.